2009
DOI: 10.1080/09540120902893258
|View full text |Cite
|
Sign up to set email alerts
|

Stressful or traumatic life events, post-traumatic stress disorder (PTSD) symptoms, and HIV sexual risk taking among men who have sex with men

Abstract: The present study assessed the presence of post-traumatic stress disorder (PTSD) symptoms in response to stressful or traumatic life events and their impact on HIV risk behaviors and associated psychosocial variables among men who have sex with men (MSM). Participants (n=189; 60% HIV-infected) who were recruited by notices posted in a community health clinic and via a modified respondent-driven sampling technique completed a behavioral assessment survey. Sixty percentage of participants screened positive for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 42 publications
(37 reference statements)
4
46
0
1
Order By: Relevance
“…Poor mental health, including depressed mood and low self-esteem, has been linked to sexual risk behavior in prior studies of adult MSM. [45][46][47] Finally, negative father-son relationship dynamics increased situational risk for some participants by predisposing them to form partnerships where they had limited power to negotiate safe sex. At its extreme, paternal rejection led to homelessness and exchanging unsafe sex in return for housing, a phenomenon that has been previously described in other gay youth.…”
Section: Discussionmentioning
confidence: 99%
“…Poor mental health, including depressed mood and low self-esteem, has been linked to sexual risk behavior in prior studies of adult MSM. [45][46][47] Finally, negative father-son relationship dynamics increased situational risk for some participants by predisposing them to form partnerships where they had limited power to negotiate safe sex. At its extreme, paternal rejection led to homelessness and exchanging unsafe sex in return for housing, a phenomenon that has been previously described in other gay youth.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in depression and decreases in wellbeing among sexually active MSM may result in externalizing symptoms, such as sensationseeking and the use of sex to avoid or alleviate negative affect, as opposed to internalizing symptoms, such as withdrawal (Alvy et al, 2011;Mustanski, 2007); these externalizing symptoms may lead to sexual risk-taking. Indeed, studies have suggested that moderately depressed individuals may regulate negative affective states by engaging in sexual behaviors (Reisner et al, 2009;Shrier et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PTSD is associated with serious sequelae, including health risk behaviors, such as unprotected sex 43 and involvement with interpersonal violence, 44 and physical sequelae, including dysregulated immune function, 45 cardiovascular risk indicators, 46 metabolic syndrome, 47 and chronic pain. 48 National surveys indicate that no more than half of people with PTSD seek treatment, 49 therefore identifying individuals at increased risk for PTSD is crucial for prevention of PTSD sequelae.…”
Section: Discussionmentioning
confidence: 99%